Synergy of Avocado Seed Meal and Expired Commercial Syrup in Enhancing Fermentation Quality of Fattening Sheep Concentrate Silage: Sinergi Tepung Biji Alpukat dan Sirup Komersial Kadaluarsa untuk Meningkatkan Kualitas Fermentasi Silase Konsentrat Domba Penggemukan (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
The use of additives plays a crucial role in providing energy sources for microorganisms during the ensiling process, enabling optimal physical quality of silage to be formed. Avocado seed meal (ASM) provides gradually released energy to support fermentative activity, while expired commercial syrup (ECS) contains easily degradable sugars that accelerate lactic acid production. The synergy between these two helps the preservation process occur more rapidly, allowing silage to reach stable conditions and exhibit better physical characteristics. This study was designed to evaluate the influence of these two materials in fattening sheep concentrate formulations, with a focus on changes in physical characteristics and acidity levels as benchmarks of fermentation success. The research was conducted using a Completely Randomized Design with five treatments and five replications, where ASM and ECS were administered at levels of 1.50%, 3%, 4.50%, and 6.00% of dry matter, while the base treatment without additives served as the control. The observed variables included silage aroma, texture, and color characteristics, as well as dry matter content, dry matter loss, pH value, and Fleigh Value as indicators of fermentation stability. The obtained data were analyzed using analysis of variance, followed by DMRT test at a 1% significance level. The research findings demonstrated that the combination of ASM and ECS had a highly significant effect (p